Clinical Studies with Anticoagulants that Have Changed Clinical Practice - Hirsh, Jack; de Vries, Tim A.C.; Eikelboom, John W.; Bhagirath, Vinai; Chan, Noel C. (Seminars in Thrombosis and Hemostasis, 2023)
Anticoagulant therapy is the cornerstone of treatment and prevention of arterial and venous thromboembolism. Taking a historical perspective, starting in the 1960s, and progressing through to 2022, we discuss key clinical trials of anticoagulants that have changed clinical practice, and examine obstacles encountered in bringing these anticoagulants to the clinic. The design of some of the early studies that shaped clinical practice was poor by current standards, but their results were influential because nothing better was available. Both heparin and vitamin K antagonists had been in clinical use for several decades before well-designed trials in the 1980s optimized their dosing and enhanced their safety and efficacy. Low-molecular-weight heparin then replaced unfractionated heparin because it had a more predictable dose–response and a longer half-life, thereby allowing it to be used conveniently in out-of-hospital settings. More recently, direct oral anticoagulants became the oral anticoagulants of choice for most indications because they were shown to be at least as safe and effective as vitamin K antagonists when used in fixed doses without the need for laboratory monitoring. The design of the trials that led to the approval of the direct oral anticoagulants was excellent, but further studies are required to optimize their dosing in selected patients who were underrepresented in these trials.
Keywords: anticoagulation; heparin; warfarin; direct oral anticoagulants; venous thromboembolism; atrial fibrillation; bleeding